Antimicrobial Acylphloroglucinol Meroterpenoids and Acylphloroglucinols from Dryopteris crassirhizoma - Hai, Ping; He, Yunqing; Wang, Ruirui; Yang, Jian; Gao, Yuan; Wu, Xudong; Chen, Nie; Ye, Li; Li, Rongtao (Planta Medica, 2022)
Ten novel meroterpenoids, dryoptins/11″-epi-dryoptins A~E (1~10) with an unprecedented skeleton consisting of dimeric or trimeric acylphloroglucinols and dehydrotheonelline, two undescribed acylphloroglucinol-nerolidol meroterpenoids (11~12), and ten known acylphloroglucinol derivatives (13~22), were isolated from D. crassirhizoma. The novel structures including absolute configurations were established by comprehensive spectroscopic analyses and quantum chemical electronic circular dichroism (ECD) calculations. A biosynthetic pathway of 1~10 was assumed. The trimeric acylphloroglucinol meroterpenoids 7/8 showed significant antifungal activity against standard Candida albicans with a MIC50 value of 1.61 µg/mL [fluconazole (FLC): 3.41 µg/mL], and when combined with FLC, the principal components 20 and 21 exhibited strong antifungal activities against FLC-resistant C. albicans with MIC50 values of 8.39 and 7.16 µg/mL (FLC: > 100 µg/mL), respectively. Moreover, compounds 2, 5/6, 18, 19, and 21 exhibited inhibitory effects against several pathogenic fungi and bacteria, with MIC50 values of 6.25 ~ 50 µg/mL.
Keywords: Dryopteridaceae; Dryopteris crassirhizoma; acylphloroglucinol-meroterpenoid; acylphloroglucinol; Candida albicans; antifungal activity